Design and application of a disposable insulin dosing container and emergency injection module (一种一次性胰岛素定量容器瓶及紧急注射组件的设计与应用) - WU Xueqiong (邬雪琼); XIONG Li (熊丽); AI Shanmu (艾山木); PANG Cuihua (庞翠华) (中西医结合护理)
Stress hyperglycemia is a common disorder of glucose metabolism in critically ill patients. Continuous micro-pump intravenous insulin infusion is an important treatment at present, and accurate insulin allocation is crucial for blood glucose management. This study introduces the design and use method of an utility model disposable insulin dosing container and emergency injection module, which can effectively improve the accuracy of insulin dosage, avoid insulin contamination, simplify the operation process, and improve the work efficiency of medical staff. (应激性高血糖是危重症患者常见的糖代谢紊乱。持续微量泵静脉输注胰岛素是重要治疗方式, 精准的胰岛素配置对于血糖管理至关重要。本研究介绍了一种实用新型一次性胰岛素定量容器瓶以及紧急注射组件的设计和使用方法, 其有效提高了胰岛素配置剂量的准确性, 简化了操作流程, 降低了胰岛素污染风险, 提高了医护人员的工作效率。)